TALEN gene knockouts reveal no requirement for the conserved human shelterin protein Rap1 in telomere protection and length regulation - Kabir, Shaheen (Cell Rep, 2014)
The conserved protein Rap1 functions at telomeres in fungi, protozoa, and vertebrates. Like yeast Rap1, human Rap1 has been implicated in telomere length regulation and repression of non-homologous end joining (NHEJ) at telomeres. However, mouse telomeres lacking Rap1 do not succumb to NHEJ. To determine the functions of human Rap1, we generated several TALEN-mediated human cell lines lacking Rap1. Loss of Rap1 did not affect the other components of shelterin, the modification of telomeric histones, the subnuclear position of telomeres, or the 3’ telomeric overhang. Telomeres lacking Rap1 did not show a DNA damage response, NHEJ, or consistent changes in their length, arguing that Rap1 does not have an important function in protection or length regulation of human telomeres. As human Rap1, like its mouse and unicellular orthologs, affects gene expression, we propose that the conservation of Rap1 reflects its role in transcriptional regulation rather than a function at telomeres.